THE EFFECT OF VIDEO-BASED EDUCATION ON POSTPARTUM MOTHERS’ KNOWLEDGE OF EXCLUSIVE BREASTFEEDING: A STUDY IN NGEMBAK VILLAGE - Sehmawati; Wahyu Dewi Hapsari (LPPM AN NUUR, 2025)
Background: The postpartum period is the phase following childbirth that lasts for approximately six weeks and coincides with the period of exclusive breastfeeding. The World Health Organization recommends that newborns receive exclusive breastfeeding for the first six months of life without any additional food or drink, as breast milk is the most natural and optimal source of nutrition for infants. Breastfeeding has also been proven to reduce the risk of breast cancer, ovarian cancer, and diabetes in mothers. According to the Grobogan Regency Health Profile in 2024, the coverage of exclusive breastfeeding reached 81.59%. Although exclusive breastfeeding coverage has met the national target in Indonesia, not all postpartum mothers practice exclusive breastfeeding due to various factors. Knowledge is one of the factors that influence exclusive breastfeeding, and educational interventions can improve postpartum mothers’ knowledge through various methods. This study provides education to postpartum mothers about exclusive breastfeeding using video-based media. Purpose ; To analyze the effect of giving video education on postpartum mothers. Methodology ; This research is a quantitative research using a quasi-experimental design with a one group pretest posttest design. The sampling he population consisted of 33 postpartum mothers, all of whom were included as samples using total sampling. Results ; showed that before the intervention, the mean knowledge score was 32.03 with a median of 33, and most respondents had a moderate level of knowledge (54.5%). After receiving video-based education, the mean knowledge score increased to 36.24 with a median of 37, and the majority of respondents demonstrated good knowledge (75.8%). The Wilcoxon test indicated a significant effect of video-based education on postpartum mothers’ knowledge of exclusive breastfeeding (p-value = 0.000). Conclusion ; Based on this research, there is an effect of giving ginger drink on breast milk production in postpartum mothers in Ngembak Village. Based on this research, there is an effect of giving ginger drink on breast milk production in postpartum mothers in Ngembak Village.